2008
DOI: 10.1088/0957-4484/19/25/255102
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity of silver nanoparticles in zebrafish models

Abstract: This study was initiated to enhance our insight on the health and environmental impact of silver nanoparticles (Ag-np). Using starch and bovine serum albumin (BSA) as capping agents, silver nanoparticles were synthesized to study their deleterious effects and distribution pattern in zebrafish embryos (Danio rerio). Toxicological endpoints like mortality, hatching, pericardial edema and heart rate were recorded. A concentration-dependent increase in mortality and hatching delay was observed in Ag-np treated emb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

23
562
3
6

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 918 publications
(594 citation statements)
references
References 32 publications
23
562
3
6
Order By: Relevance
“…In these studies, the particles are typically found to be agglomerated/aggregated, for example, TiO 2 [53,62,65,66], ZnO [43,53,[66][67][68], Ag [23,69], SiO 2 [70], and CeO 2 [53]. Manzo et al [71] analyzed an ZnO NP-contaminated soil by the Brunauer-Emmett-Teller method and found that the particles were not aggregated.…”
Section: Soil Propertiesmentioning
confidence: 99%
“…In these studies, the particles are typically found to be agglomerated/aggregated, for example, TiO 2 [53,62,65,66], ZnO [43,53,[66][67][68], Ag [23,69], SiO 2 [70], and CeO 2 [53]. Manzo et al [71] analyzed an ZnO NP-contaminated soil by the Brunauer-Emmett-Teller method and found that the particles were not aggregated.…”
Section: Soil Propertiesmentioning
confidence: 99%
“…In contrast, surface-enhanced Raman scattering (SERS) technique can amplify Raman signals up to 10 14 folds using metallic surfaces [e.g., silver (Ag) and gold] [6]. The SERS strategy has also demonstrated in vivo Raman measurements with penetration deeper than 700 mm, but the subcutaneous injection of metal nanoparticles can be toxic [7]. Though the use of SERS-active acupuncture needles can eliminate the need of nanoparticle injection [8], these needles are still required to be pulled out from the subject for SERS measurements and skillful needle administration is needed [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Earlier, PVP stabilized AgNPs were found to upregulate/down-regulate various processes in Chlamydia trachomatis [16]. Various reports on antioxidant system defense, show that oxidative stress is the primary mechanism for toxicity of AgNPs, wherein accumulation of AgNPs in the nucleus is responsible for genomic damage and instability which consequently lead to DNA damage and apoptosis, facilitating mortality [16,17].…”
Section: Amplification Of Antioxidant Bio-marker Enzyme Genesmentioning
confidence: 99%